Efektivitas Kepemimpinan Kepala Sekolah dalam Meningkatkan Kemampuan Guru Menyusun RPP di MAS Al-Ikhwan Serapuh - Satria Wiguna; Rani Febriyanni; Novira Arafah; Rizki Akmalia (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
The specific objectives of this research are to: 1). Knowing the Principal's Leadership at Al-Ikhwan Assalam Islamic Boarding School; 2). Knowledge of the principal's socialism in leading the Al-Ikhwan Assalam Islamic Boarding School. 3). Knowing the professionalism of the leadership of school principals at the Al-Ikhwan Assalam Islamic Boarding School; 4). Finding and analyzing the effectiveness of the principal's leadership in improving teacher competence on lesson plans at the Al-Ikhwan Assalam Islamic Boarding School. This type of qualitative research with a descriptive approach. Methods of collecting data by means of observation, interviews and documentation. Techniques of data analysis by reduction, data presentation, drawing conclusions or verification. The results of the research and discussion show that from the socialism perspective of the principal, it is known that the principal's social competence is in establishing good relationships with internal and external parties of the school. In terms of Managerial Leadership in the ability of teachers to prepare lesson plans by providing directions, instructions for implementing learning, supervision and evaluation of activities, in terms of the ability of school principals who are able to protect, provide examples and solve problems and achievements at the MAS Al-Ikhwan Assalam school. The Effectiveness of Principal Leadership in Improving Teacher Competence, RPP, the results show that most teachers are able to be independent in making and compiling lesson plans.